PEMANFAATAN PROGRAM KELUARGA HARAPAN DI KABUPATEN PESISIR SELATAN - Ekardo, Apando; Putri, Desi Eka; Sari, Tiara Indah; Ramadhani, Ramadhani; Jahara, Nila (Jurnal Manajemen Pendidikan, 2024)
The Family Hope Program (PKH) is one of the poverty alleviation programs launched by the government in 2007 and has been ongoing until now. However, there are several problems in its implementation, including: fund distribution, the length of time for fund disbursement, and not all poor people receive PKH assistance. This study aims to see the contribution of the utilization of the Family Hope Program (PKH) assistance funds in poverty alleviation in Pesisir Selatan Regency; obstacles faced in the utilization of assistance funds (PKH); and strategies for utilizing assistance funds (PKH) to be more effective. This study uses a qualitative approach. Data was collected through observation, interviews and documentation studies. Informants were selected using purposive sampling. The results of this study show the contribution of the utilization of assistance funds (PKH) in poverty alleviation in Pesisir Selatan Regency. In the fields of education and health, it has been realized well. The obstacles faced in the utilization of assistance funds (PKH) in Pesisir Selatan Regency, namely the length of time for fund disbursement, hampered Households (KPM) in buying school uniforms for their children, so they borrowed money before the funds were disbursed. The strategy for utilizing assistance funds (PKH) to be more effective is to conduct outreach to KPM and provide a clear understanding so that they understand the objectives of the program as well as the government's monitoring and evaluation of the program.